2015
DOI: 10.1016/j.jfa.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Fock space associated to Coxeter groups of type B

Abstract: In this article we construct a generalized Gaussian process coming from Coxeter groups of type B. It is given by creation and annihilation operators on an (α, q)-Fock space, which satisfy the commutation relationwhere x, y are elements of a complex Hilbert space with a self-adjoint involution x →x and N is the number operator with respect to the grading on the (α, q)-Fock space. We give an estimate of the norms of creation operators. We show that the distribution of the operators b α,q (x) + b * α,q (x) with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…The type B Gaussian elements of [BEH15] 'live' in the algebra of bounded linear operators on a deformed Fock space. We briefly outline their construction and its context.…”
Section: Noncommutative Probability and The Type B Gaussian Statisticsmentioning
confidence: 99%
“…The type B Gaussian elements of [BEH15] 'live' in the algebra of bounded linear operators on a deformed Fock space. We briefly outline their construction and its context.…”
Section: Noncommutative Probability and The Type B Gaussian Statisticsmentioning
confidence: 99%
“…Let us point out some of the keys to calculate the distribution of G α,q (f ) in [BEH15]. It is shown that a linear map, Φ :…”
Section: Key Ideas and Our Purposementioning
confidence: 99%
“…The (α, q)-inner product on the full Fock space F (H) is defined by The readers can consult [BEH15] for details.…”
Section: Lemma 39 ([Mgh90])mentioning
confidence: 99%
See 2 more Smart Citations